Contradições e conflitos na atuação de empresas e do INSS no processo de retorno ao trabalho de trabalhadores afastados por LER/DORT - Silva, Elaine Cristina (Universidade Federal de São Carlos, 2016)
Manifestations Work-Related Musculoskeletal Disorders (WRMSDs) in the workplace have been of concern, as its growth has forced the society to deal with this problem high economic impact due to the significant increase in the number of absences related to work. After diagnosis and removal, the INSS medical expert, according to conditions / worker capabilities, forwards it to the Vocational Rehabilitation Program INSS, which should provide the means of professional and social rehabilitation, according to the Federal Constitution. However, the difficulties of the Ministry of Social Security in return method of workers away by WRMSDs has been the subject of discussion. This study aimed to understand of the process of return to the employee's work away for WRMSDs, through the activity of ergonomics, focusing on the need for interaction between business, labor and INSS. The methodology was designed / led by a return to work flow chart created by the researcher from the model of inclusion of people with disabilities of Simonelli (2009). The methodology consisted initially of approval of UFSCar's Ethics Committee for the collection and analysis of data in the four companies that agreed to participate, and Term of Consent of workers. For data collection, the workers were interviewed, underwent evaluation capacity for work, from protocols and core set of ICF and were followed in jobs for systematic observation and understanding of the activity, as a presupposition of ergonomics activity. In the study of different cases it was found that the activities analyzed show that the removal station for reintegration post significant changes. Some study companies have a program for approaching the worker in the period of clearance. The professional courses offered by the INSS, mostly do not meet the requirements of the tasks of the companies, therefore, do not help the worker in the process of returning to work. The worker who returns clearance, is generally placed in the position that the company chooses, since it seeks to meet the restrictions that the Vocational Rehabilitation Program prescribes. However, this does not help you during the process of reintegration and skilled professionals of the company did not accompany him regularly. With the observed situations, it is concluded that the actual return depends on the joint work of these three social actors (company, employee and Vocational Rehabilitation), which complement each other, including analysis of activity in the stations selection process for inclusion, aiming discussions generate fruits that benefit workers and, consequently, companies and the INSS.
Keywords: Trabalhador; LER/DORT; Retorno ao trabalho; INSS; Empresa; Ergonomia da atividade; Worker; Return to work; Company; Activity of ergonomics; ENGENHARIAS::ENGENHARIA DE PRODUCAO